Early Actions of Neurotransmitters During Cortex Development and Maturation of Reprogrammed Neurons - Ojeda, Jorge; Ávila, Ariel (Frontiers in Synaptic Neuroscience, 2019)
The development of the brain is shaped by a myriad of factors among which neurotransmitters play remarkable roles before and during the formation and maturation of synaptic circuits. Cellular processes such as neurogenesis, morphological development, synaptogenesis and maturation of synapses are temporary and spatially regulated by the local or distal influence of neurotransmitters in the developing cortex. Thus, research on this area has contributed to the understanding of fundamental mechanisms of brain development and to shed light on the etiology of various human neurodevelopmental disorders such as autism and Rett syndrome, among others. Recently, the field of neuroscience has been shaken by an explosive advance of experimental approaches linked to the use of induced pluripotent stem cells and reprogrammed neurons. This new technology has allowed researchers for the first time to model in the lab the unique events that take place during early human brain development and to explore the mechanisms that cause synaptopathies. In this context, the role of neurotransmitters during early stages of cortex development is beginning to be re-evaluated and a revision of the state of the art has become necessary in a time when new protocols are being worked out to differentiate stem cells into functional neurons. New perspectives on reconsidering the function of neurotransmitters include opportunities for methodological advances, better understanding of the origin of mental disorders and the potential for development of new treatments.